2010
DOI: 10.1111/j.1479-828x.2009.01119.x
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle factors in people seeking infertility treatment – A review

Abstract: Advice on modifiable lifestyle factors should be given to people presenting for infertility treatment to help them make positive changes that may improve their chances of pregnancy and delivering a healthy, live baby. Developing a guideline for this would be a prudent step towards helping clinicians to implement this aspect of preconception care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
146
3
7

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 244 publications
(158 citation statements)
references
References 145 publications
(186 reference statements)
2
146
3
7
Order By: Relevance
“…Most studies on stress and in vitro fertilization have identified a relationship between higher stress levels and a lower percentage of pregnancy and livebirths [18][19][20]. Stress exposure itself has even been directly related to conceptive failure [14] and considered as the most common reason for fertility treatment interruption [21].…”
Section: Infertilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies on stress and in vitro fertilization have identified a relationship between higher stress levels and a lower percentage of pregnancy and livebirths [18][19][20]. Stress exposure itself has even been directly related to conceptive failure [14] and considered as the most common reason for fertility treatment interruption [21].…”
Section: Infertilitymentioning
confidence: 99%
“…The low success rate of ARTs makes these "solutions" a source of various stress factors which build up throughout the different treatments. IVF treatment, specifically, may become a long, painful and stressful process, during which frustration due to unfulfilled expectations, social pressure, helplessness, disappointment, hopelessness and downheartedness because of failure and the economic costs of the process may arise [14,15].…”
Section: Infertilitymentioning
confidence: 99%
“…2. Male partners should stop smoking, and limit alcohol use to 3-4 units/week, and abstain from illicit drug use [136,137]. 3.…”
Section: Counseling Of Male Infertile Patientsmentioning
confidence: 99%
“…Prescribe exercise and weight loss for overweight or obese men. A healthy BMI ranges from 20 to 27 [137][138][139]. 4.…”
Section: Counseling Of Male Infertile Patientsmentioning
confidence: 99%
“…Давно известно не-гативное влияние на состояние репродуктивной сис-темы таких факторов, как употребление алкоголя, курение, прием наркотических препаратов [5,6]. В 30-40 % случаев причину мужского бесплодия выявить не удается, такие формы относят к идиопатическому бес-плодию, объединяющему множество разных по пато-генезу состояний [7].…”
unclassified